(untitled) (Islas, 2023)
Introduction: The arrival of the Central Railway in Camagüey in 1902 constitutes a significant event for the socioeconomic development of the province between 1902 and 1925. However, it is noted that there is still insufficient knowledge about the implications brought about by this event. Methods: Knowledge methods such as analysis-synthesis, historical-logical analysis, and document analysis are applied. Results: As a result of the study, the main implications of the Central Railway in the development of the Camagüey territory between 1902 and 1925 are systematized. Conclusions: The development of the sugar industry, the construction of railway infrastructure that has a positive impact on the lives of the population, and the struggles of workers against the injustices of railway companies.